Clinical Use of Cinacalcet in MEN1 Hyperparathyroidism - V. J. Moyes; J. P. Monson; S. L. Chew; S. A. Akker (International Journal of Endocrinology)
Background. Management of multiple-endocrine neoplasia type 1- (MEN1-) associated hyperparathyroidism is associated with high recurrence rates and high surgical morbidity due to multiple neck explorations. Cinacalcet, a calcimimetic agent licensed for the treatment of secondary hyperparathyroidism and parathyroid carcinoma, may provide a medical alternative for the management of these complex patients. Methods. A prospective audit was performed of eight patients; three males and five females, aged 20–38 at diagnosis. Two patients commenced cinacalcet as primary treatment and six had previous surgery. Six patients had complications of hyperparathyroidism: renal calculi, renal dysfunction, and reduced bone mineral density. All were commenced on cinacalcet 30 mg bd for MEN1 associated hyperparathyroidism; doses were subsequently reduced to 30 mg od in four patients. Results. Significant reductions were observed in serum calcium and PTH measurements. Serum calcium reduced by a median of 0.35 mmol/L (𝑃=.012 Wilcoxon Signed Rank). Serum PTH levels decreased by a median of 5.05 pmol/L (𝑃=.012). There was no change in urine calcium. Duration ranged from 10–35 months with maintenance of control. Cinacalcet was well tolerated by six patients; one experienced nausea and one experienced diarrhoea. Conclusion. Cinacalcet is an effective and well-tolerated medical treatment for the management of complex primary hyperparathyroidism.